MOBILE PAYMENT SATISFACTION POST PANDEMIC COVID-19 IN INDONESIA - Muhammad Nurhaula Huddin Huddin; Khairul Ikhsan (Universitas Airlangga, 2022)
This study aims to examine the effect of technology security, ease of use, usability, and continuousimprovement on the satisfaction of mobile payment users. This study uses a purposive sampling techniquewith certain criteria. The population of this study are respondents who have used m-payment services duringthe Covid-19 pandemic from 2020 to 2021 in Indonesia. Questionnaires were distributed through an onlinesurvey method with a total sample of 317 respondents. Hypothesis testing was carried out using StructuralEquation Modeling (SEM) AMOS 23. The results showed that technology security had a positive effect onmobile payment satisfaction, ease of use had a positive effect on mobile payment satisfaction, usability had apositive effect on mobile payment satisfaction, continuous improvement had a positive effect on satisfactionmobile payments, and satisfaction have a positive effect on the trustworthiness of mobile payments. Thisresearch provides information to payment service providers to continuously improve improvements in allaspects of services, especially security and ease of use, as well as benefits for consumers in conductingfinancial transactions.